The Dynamics Of Language And Identity In Donald Trump’s Victory Speech: A Discourse Analysis - Aulia Citra Dewi (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2025)
This study examines how Donald Trump constructs political identity and legitimizes ideological power through language in his 2016 victory speech by applying Fairclough’s Critical Discourse Analysis (CDA). While previous studies have largely focused on campaign discourse, this research highlights the victory speech as a transitional discourse between persuasion and presidential legitimacy. A qualitative descriptive method was employed, analyzing the speech through textual, discursive, and social dimensions. The findings indicate that Trump strategically uses inclusive pronouns, repetition, metaphor, modality, and simple syntax to construct collective identity, reinforce nationalist ideology, and legitimize authority. The discourse reflects populist tendencies, particularly through the construction of “the people” and a narrative of national restoration. The study concludes that political discourse functions as a strategic tool for shaping identity, ideology, and power relations.